Peran Artificial Intelligence (AI) dalam Pembelajaran Bahasa Arab Mahasiswa Pascasarjana UIN Maulana Malik Ibrahim Malang - Evy Nur Rohmawaty; Danial Hilmi; M Sholih Salimul Uqba; Ummu Sulaimah Saleh (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The development of Artificial Intelligence (AI) technology such as Chatbots, virtual assistants, machine translation, natural language processing, GPT chat, You AI, and Google Bardi have had a significant impact on Arabic language learning for postgraduate students at UIN Maulana Malik Ibrahim Malang. The aim of this research is to identify the various AI applications used by students, as well as to evaluate the extent to which AI contributes to enriching their learning experience. The results of this research are that AI tools facilitate more interactive learning, encourage easy access to information, and increase efficiency in understanding Arabic. AI provides immediate feedback, helps translate text, and provides extensive reference resources, providing a richer and more affordable learning experience. Through its multifunctional role, AI has opened the door to a more personalized, adaptive and effective learning approach in mastering the Arabic language. This reflects the role of technology in supporting students in achieving a deeper understanding of the language, marking an important milestone in the development of Arabic language education at UIN Maulana Malik Ibrahim Malang.